A reformation Study about the Construction Management in the Primary Stage Curricula’s for the Civil Engineering in Some of the Iraqi Universities (Journal of Engineering, 2016)
There is no doubt that the field of education and teaching (in any country and whatever its ruling system varies “d”) is considered one of the most specific and sensitive field, because it is related to the building of human. And as the human is a purpose (aim) and the means in the same time and he is the strategist capital, so he way of his rearing, education, choosing the educator, methods of working and the aims are considered serious matters.     The educational process has aim determined by the society for him self through its working establishments in this field and these are the official and public establishments. And as he feels that the establishments have failed to achieve its duty, it, and without hesitation immediately interferes by the means that he choose to fix the defect. The educational process aims are meant to be the determined modification for the way which are expected to change the students through this process .i,e. the way of their thinking, feeling and actions. And the curricula’s used (followed) are considered one of the means to achieve the aims.     This research aims at studying the program of the construction management wherefrom the items are distributed although the years and hours of primary stage in the civil engineering department in Baghdad university and some other Iraqi universities. The curricula’s items of some sedate worldwide (universal) universities, and to make a comparison between them to reach a specific form to the method of teaching these items, unify them, revive them and to contribute in clarifying the features of the path way ahead of a teaching Corp member which is followed in the teaching curricula’s of the construction on the means which make achieving this complicated process a living interactive system.